Biodegradation of Naphthalene by Aspergillus flavus Before and After Exposing to UV Light - Al Fayaad , Duha Bahaa Mohammed; A.Al-A’adhmi , Mohammed; Al Fatlawy, Yaaroub Faleh (Iraqi Journal of Science, 2022)
Aspergillus flavus was tested for its ability to degrade naphthalene by using solid mineral salts medium (SMS) with different concentrations 100, 300, 500 ppm of naphthalene. Results showed that 100ppm was the best concentration consumed by the fungal test then 300ppm and 500ppm the results for secondary test by using Liquid Mineral Salts Medium (LMSM) 95% of degradation for 100ppm then75% for 300ppm and 30% of degradation for 500ppm then the fungal test was tested for its ability to produce lignolytic enzymes results revealed that lignin peroxidase enzyme was only produced .then fungal test exposed to U.V light and the result showed after 10 minutes of U.V light exposure the degradation ratio were 91% for 100ppm then 79% for 300ppm and 73% for 500ppm.After 20 minutes of U.V light exposure the results showed 93% for 100ppm, 84% for 300ppm and 80% for 500ppm.